2005
DOI: 10.1080/00365540510038497
|View full text |Cite
|
Sign up to set email alerts
|

A multi-centre prospective study of febrile neutropenia in Norway: Microbiological findings and antimicrobial susceptibility

Abstract: The urgent need to treat presumptive bacterial or fungal infections in neutropenic patients has meant that initial therapy is empiric and based on the pathogens most likely to be responsible, and drug resistance. The traditional empirical treatment in Norway has been penicillin G and an aminoglycoside, and this combination has been criticized over recent y. We wished to analyse the microbiological spectrum and susceptibility patterns of pathogens causing bacteraemia in febrile neutropenic patients. This was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
2
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 44 publications
3
22
2
8
Order By: Relevance
“…Thus, results were relatively similar except for ampicillin, ceftazidime, and amikacin. Sigurdardottir et al found that 57% of coagulase-negative staphylococci were oxacillin resistant (9). Moreover, no oxacillin resistant S. aureus isolate was observed, whereas, in this study, 88% of coagulase-negative staphylococci isolates and 77.3% of S. aureus strains were oxacillin resistant.…”
Section: (1)contrasting
confidence: 48%
“…Thus, results were relatively similar except for ampicillin, ceftazidime, and amikacin. Sigurdardottir et al found that 57% of coagulase-negative staphylococci were oxacillin resistant (9). Moreover, no oxacillin resistant S. aureus isolate was observed, whereas, in this study, 88% of coagulase-negative staphylococci isolates and 77.3% of S. aureus strains were oxacillin resistant.…”
Section: (1)contrasting
confidence: 48%
“…In the 70`s, in monomicrobial bacteremia, these bacteria mainly consisted of Gram-negative ones while with the advent of Coagulase-negative staphylococci (CoNS), Viridans streptococci, and Enterococci, this pattern changed to Gram-positive organisms in the 80`s and 90`s (7)(8)(9). In a comparison of febrile neutropenic children with adults, it was demonstrated that 64.2% and 57.9% of isolates were Gram positive in children and adults, respectively (10).…”
Section: Introductionmentioning
confidence: 99%
“…Llama la atención el alto porcentaje de óbitos (17,1%) con respecto a estudios realizados tanto en (17)(18)(19) nuestro país como en el extranjero . Este tema debería investigarse a profundidad en estudios prospectivos.…”
Section: Discussionunclassified